Pengaruh Ukuran Pemerintah Daerah, Tingkat Ketergantungan Pemerintah Daerah, Opini Audit, dan Temuan Audit terhadap Audit delay - Gemilang, Yogyaria Astin Kartika; Pramita, Yulinda Devi (Universitas Muhammadiyah Magelang, 2021)
This study aims to analyze the effect of government size, dependence on governmental grants, audit opinion, and audit findings on audit delay. The samples of this study were audit reports of provincial government from 2015 to 2019. The obtained data were 167. The data collection method used in this study was purposive sampling. This study used multiple linear regression analysis. The results of this study showed that government size and dependence on governmental grant had no significant effect on audit delay, while audit opinion and audit findings had a positive and significant effect on audit delay.